X mode Doppler reflectometry k-spectral measurements in ASDEX Upgrade: experiments and simulations. (24th May 2017) - Lechte, C; Conway, G D; Görler, T; Tröster-Schmid, C
Abstract: The perpendicular density fluctuation spectrum in the tokamak ASDEX Upgrade was measured with Doppler reflectometry. In this paper, extensive plasma turbulence and microwave propagation simulations with thegene gyro-kinetic code and theipf-fd3d full-wave code were undertaken to explain the observed spectral shape. It was shown that in this case the X-mode polarisation suffers both from a large nonlinear saturation effect at low-to-intermediate probed wavenumbers, and a super-linear enhancement effect at large wavenumbers. With these effects, we were able to explain the observed discrepancies between thegene perpendicular wavenumber spectra and the Doppler reflectometry derived wavenumber spectra. While the agreement is not perfect, the simulations give guidance on how to interpret X-mode Doppler reflectometry spectra.